Pengaruh Rasio Na2SiO3/NaOH sebagai Alkali Aktivator Terhadap Hilang Pijar dan Kehalusan Butiran Semen (Blaine Analysis) Geopolimer Berbasis Tanah Napa - Vira Nilmania; Mawardi Mawardi (Departemen Kimia FMIPA UNP, 2022)
Geopolymer is a material or binder that synthesized by mixing alumina silicate source material and alkaline activator solution. One of the source materials for alumina silicate is napa soil that contained hight amount of SiO2 dan Al2O3 with percentage 62,70% and 31,16% of XRF analysis after calcination, that can be used as material based of geopolymer. The aims of calcination is to increase the surface area of the aluminasilica material so that it can increase the maximum solubility of aluminasilica by alkaline activator. This study reports lost of ignition and blaine analysis of napa soil-based geopolymer cement with variations in alkali activator ratio Na2SiO3/NaOH is 1, 1.5, 2, 2.5. The charactization of napa soil-based geopolymer cement indicated the optimum lost of ignition and blaine analysis on the ratio Na2SiO3/NaOH is 2,5 which is 6,63% and 725 m2/kg, it is higher than ordinary cement based on SNI with minimum blaine analysis is 280 m2/kg.